Polysulfonate film composite film and preparation method thereof
By conducting interfacial polymerization of multi-hydroxyl monomers and multi-sulfonyl chloride monomers on the surface of a porous support membrane, a polysulfonate film composite membrane was prepared. This solved the problems of easy hydrolysis of polyamide films under acidic conditions and difficulty in pore size control, and achieved a film material with high acid resistance and environmental protection performance, which is suitable for applications such as seawater desalination and water treatment.
Patent Information
- Application Number
- CN202510793167.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-10-31
AI Technical Summary
Existing polyamide film composite membranes are prone to hydrolysis under acidic conditions and are affected by changes in solution pH, resulting in poor acid resistance and environmental performance, and it is difficult to finely control the pore size.
A polysulfonate film composite membrane was prepared by interfacial polymerization of multi-hydroxyl monomers and multi-sulfonyl chloride monomers on the surface of a porous support membrane. The interfacial reaction was controlled by selective surfactants to form a uniform polysulfonate separation layer.
It improves the acid resistance and environmental performance of polysulfonate film composite membranes, enabling them to maintain a high rejection rate in acidic environments and control the pore size within the range of nanofiltration and reverse osmosis, making them suitable for seawater desalination, water treatment and other fields.
Smart Images

Figure CN120860838A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thin film composite film technology, specifically to a polysulfonate thin film composite film and its preparation method. Background Technology
[0002] Thin-film composite membranes prepared by interfacial polymerization of polyamines and polyacrylamide chlorides have been widely studied and used in separation processes such as reverse osmosis and nanofiltration. These membrane composites typically exhibit good permeability and selectivity; however, the amide bonds in the polyamide molecular chain are easily hydrolyzed under acidic conditions, affecting the structural stability of the membrane during long-term use. Furthermore, under acidic conditions, the ionization of charged groups on the nanofiltration membrane surface is easily affected by changes in the solution environment; for example, when the solution pH changes, the retention capacity of the nanofiltration membrane for charged solutes changes accordingly. These factors significantly limit the application of traditional polyamide membrane composites in the separation of acidic wastewater.
[0003] In the prior art, polysulfonamides have a higher steric hindrance effect due to the smaller S=O bond angle in sulfonamides compared to C=O bonds in amides, making them less susceptible to H2O. + The S=O group is more stable than the C=O group due to its attack capability. Furthermore, the strong conjugation effect between the sulfonyl group and the benzene ring gives the polysulfonamide structure both thermal and chemical stability, making it more resistant to H₂O. + The attack of sulfonamides demonstrates superior acid resistance compared to polyamides. Furthermore, by introducing triazine ring structures to construct polyamine-based composite membranes, the acid resistance of the material can also be improved. However, sulfonamide materials still use polyamines as the reaction unit, resulting in poor environmental performance of polysulfonate composite membranes prepared based on sulfonamide materials. Moreover, triazine ring-based compounds suffer from uneven functional group reactivity during the reaction process, limiting controllability in the preparation of composite membranes. Therefore, it is difficult to obtain composite membranes with finely controlled pore sizes within the nanofiltration and reverse osmosis pore size range. Summary of the Invention
[0004] One objective of the first aspect of this invention is to provide a polysulfonate film composite film that solves the technical problem of poor acid resistance and environmental friendliness of polyester film composite films in the prior art.
[0005] Another objective of the first aspect of this invention is to improve the quality and separation performance of polysulfonate film composite membranes.
[0006] The second objective of this invention is to provide a method for preparing the above-mentioned polysulfonate film composite film.
[0007] According to a first aspect of the present invention, the present invention provides a polysulfonate film composite membrane, comprising a porous support membrane and a polysulfonate separation layer, wherein the polysulfonate separation layer is prepared by interfacial polymerization of an aqueous solution and an oil solution; wherein...
[0008] The aqueous phase solution comprises a polyhydroxy monomer and a selectively added first surfactant, and the oil phase solution comprises a polysulfonyl chloride monomer and a selectively added second surfactant.
[0009] Optionally, the polyhydroxy monomer includes any one or a combination of two or more of the following: tannic acid, protocatechuic acid, gallic acid, ellagic acid, anthocyanin, proanthocyanidins, bisphenol A, epigallocatechin gallate, epigallocatechin, gallocatechin, gallocatechin gallic acid, catechuic acid, epicatechin, epicatechin gallate, quercetin, curcumin, cyclodextrin, sodium alginate, and resveratrol.
[0010] Optionally, the first surfactant is a water-soluble surfactant, which includes any one or a combination of two or more of quaternary ammonium salt surfactants and heterocyclic surfactants.
[0011] Optionally, the quaternary ammonium salt surfactant includes any one or a combination of two or more of the following: octaalkyltrimethylammonium chloride, octaalkyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, docosyltrimethylammonium chloride, and docosyltrimethylammonium bromide.
[0012] Optionally, the second surfactant comprises any one or a combination of two or more of the following: bis(octadecyl)dimethylammonium chloride, bis(octadecyl)dimethylammonium bromide, bis(hexadecyl)dimethylammonium chloride, bis(hexadecyl)dimethylammonium bromide, bis(dodecyl)dimethylammonium chloride, bis(dodecyl)dimethylammonium bromide, bis(decyl)dimethylammonium chloride, bis(octadecyl)dimethylammonium bromide, and bis(octadecyl)dimethylammonium chloride.
[0013] Optionally, the porous support membrane is a polyethersulfone ultrafiltration membrane.
[0014] Optionally, the thickness of the polysulfonate separation layer is any value between 10 nm and 300 nm.
[0015] According to a second aspect of the present invention, the present invention also provides a method for preparing the polysulfonate film composite film according to any one of the above claims, characterized in that it comprises the following steps:
[0016] An aqueous solution containing multiple hydroxyl monomers is coated onto the surface of a porous support membrane and left to stand for a first preset time under a first preset temperature and preset relative humidity conditions.
[0017] An oil phase solution containing polysulfonyl chloride monomers is coated onto the surface of the porous support membrane and left to stand for a second preset time to prepare a composite membrane.
[0018] The composite film is annealed to obtain a polysulfonate film composite film; wherein...
[0019] The first preset temperature is any value between 15℃ and 40℃, the preset relative humidity is any value between 20% and 80%, the annealing temperature is any value between 30℃ and 90℃, and the annealing time is any value between 5min and 60min.
[0020] Optionally, the concentration of the polyhydroxy monomer in the aqueous solution is any value between 0.5 g / L and 40 g / L.
[0021] Optionally, the concentration of the polysulfonyl chloride monomer in the oil phase solution is any value between 0.5 g / L and 30 g / L.
[0022] This invention utilizes the interfacial polymerization reaction between polyhydroxy monomers in an aqueous solution and polysulfonyl chlorides in an oil solution on the surface of a porous support membrane. Specifically, the porous support membrane serves as the supporting interface, allowing the polyhydroxy monomers in the aqueous solution and the polysulfonyl chloride monomers in the oil solution to undergo interfacial polymerization at the water / oil interface. This process produces a polysulfonate film composite membrane with excellent acid resistance and environmental performance, which can maintain a sodium chloride rejection rate of over 97% even after immersion in a 10% (w / v) sulfuric acid solution.
[0023] Furthermore, the first surfactant of the present invention is a water-soluble surfactant, which can effectively reduce the surface tension of the aqueous solution, so that the polyhydroxy monomers are uniformly distributed on the surface of the porous support membrane, which helps to improve the uniformity of the subsequent interfacial polymerization reaction, thereby improving the quality and separation performance of the polysulfonate film composite membrane.
[0024] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0025] The following sections will describe some specific embodiments of the invention in detail by way of example and not limitation, with reference to the accompanying drawings. The same reference numerals in the drawings denote the same or similar parts or portions. Those skilled in the art should understand that these drawings are not necessarily drawn to scale. In the drawings:
[0026] Figure 1 This is a schematic flowchart of a polysulfonate film composite film according to an embodiment of the present invention;
[0027] Figure 2 These are TEM images of the polysulfonate film composite membranes prepared in Examples 3-5 of the present invention;
[0028] Figure 3 The basis is the AFM diagram of the polysulfonate film composite film prepared in Examples 3-5 of the present invention;
[0029] Figure 4 This is a test diagram of the acid resistance of the polysulfonate film composite film prepared in Example 3 of the present invention;
[0030] Figure 5 This is a test diagram of the acid resistance of the polysulfonate film composite film prepared in Example 4 of the present invention. Detailed Implementation
[0031] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and are not intended to limit the scope of the invention.
[0032] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, it should be noted that, for ease of description, only the parts relevant to this application are shown in the accompanying drawings, not the entire structure. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this application.
[0033] The terms “comprising” and “having”, and any variations thereof, used in this application are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not limited to the steps or units listed, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to such process, method, product, or apparatus.
[0034] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0035] like Figure 2 As shown, this invention provides a polysulfonate film composite membrane, comprising a porous support membrane and a polysulfonate separation layer. The polysulfonate separation layer is prepared by interfacial polymerization of an aqueous solution and an oil solution. The aqueous solution comprises a poly(hydroxyl) monomer and a selectively added first surfactant, while the oil solution comprises a poly(sulfonyl chloride) monomer and a selectively added second surfactant. Here, the first surfactant may be selectively added to the aqueous solution used to prepare the polysulfonate separation layer, or it may be selectively omitted; similarly, the second surfactant may be selectively added to the oil solution, or it may be selectively omitted.
[0036] In this embodiment, the interfacial polymerization reaction between the polyhydroxy monomers in the aqueous solution and the polysulfonyl chlorides in the oil solution occurs on the surface of a porous support membrane. That is, the porous support membrane serves as the supporting interface, allowing the polyhydroxy monomers in the aqueous solution and the polysulfonyl chloride monomers in the oil solution to undergo interfacial polymerization at the water / oil interface, thereby preparing a polysulfonate film composite membrane. The polysulfonate film composite membrane prepared in this embodiment has excellent acid resistance and environmental friendliness, and can still maintain a sodium chloride rejection rate of over 97% after being immersed in a 10% (w / v) sulfuric acid solution.
[0037] In this embodiment, the effective molecular weight cutoff of the polysulfonate film composite membrane can be adjusted within the range of 100 Da to 2000 Da, which can meet the separation requirements of ions and molecules in different scenarios. For example, the polysulfonate film composite membrane can be used in seawater desalination, water treatment, chemical liquid treatment and concentration, hemodialysis, drug separation, food processing, or environmental protection. Here, the effective molecular weight cutoff of the polysulfonate film composite membrane prepared in this embodiment can be 100 Da, 150 Da, 200 Da, 500 Da, 1000 Da, 1500 Da, or 200 Da, or any value within the range of 100 Da to 2000 Da.
[0038] In this embodiment, the first surfactant in the aqueous solution generates an electrostatic interaction with the polyhydroxy monomer to form an ion pair. The ion pair further reacts with the polysulfonyl chloride monomer in the oil solution through an interfacial polymerization reaction to form a polysulfonate separation layer. The polysulfonate separation layer is formed on the surface of the porous support membrane that serves as the support layer, so as to prepare a polysulfonate film composite membrane with different pore sizes.
[0039] In a further embodiment, the polyhydroxy monomer includes any one or a combination of two or more of the following: tannic acid, protocatechuic acid, gallic acid, ellagic acid, anthocyanins, proanthocyanidins, bisphenol A, epigallocatechin gallate, epigallocatechin, gallocatechin, gallocatechin gallic acid, catechin acid, epicatechin, epicatechin gallate, quercetin, curcumin, cyclodextrin, sodium alginate, and resveratrol. The polyhydroxy monomers in this embodiment are all natural hydroxyl compounds, possessing abundant hydroxyl groups and being environmentally friendly natural compounds. These abundant hydroxyl groups can undergo nucleophilic reactions with polysulfonyl chloride monomers, promoting interfacial polymerization. Furthermore, since tannic acid, catechin, and gallic acid possess natural antioxidant and antifouling properties, they can improve the antioxidant and self-cleaning properties of the polysulfonate film composite membrane, thereby ensuring the service life of the polysulfonate film composite membrane. Furthermore, resveratrol and anthocyanins in the polyhydroxy monomers possess strong UV resistance, effectively inhibiting the degradation of polysulfonate film composites under prolonged UV exposure, thus helping to extend the service life of polysulfonate film composites in outdoor or sun-exposed applications. Regarding the selection of polyhydroxy monomers, monomers with corresponding properties can be chosen based on specific requirements.
[0040] In a further embodiment, the first surfactant is a water-soluble surfactant, which includes any one or a combination of two or more of quaternary ammonium salt surfactants and heterocyclic surfactants. In this embodiment, the quaternary ammonium salt surfactant is a type of cationic surfactant that can effectively reduce the surface tension of the aqueous solution, allowing the polyhydroxy monomers to be uniformly distributed on the surface of the porous support membrane, which helps to improve the uniformity of the subsequent interfacial polymerization reaction, thereby improving the quality and separation performance of the polysulfonate film composite membrane. In addition, the quaternary ammonium salt surfactant has cationic properties, which can enhance the interfacial affinity between the aqueous and oil phases through electrostatic adsorption, promote the rapid nucleation and growth of polymer chains, and improve the density and selectivity of the polysulfonate separation layer.
[0041] In a further embodiment, the quaternary ammonium salt surfactant includes any one or a combination of two or more of the following: octaalkyltrimethylammonium chloride, octaalkyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, docosyltrimethylammonium chloride, and docosyltrimethylammonium bromide. In this embodiment, the quaternary ammonium salt surfactant can reduce the interfacial tension at the interface between the aqueous and oil phases, making the interfacial polymerization reaction more rapid and uniform, thereby promoting the growth of polymer chains and ultimately improving the overall quality and structural uniformity of the membrane. Furthermore, the cationic nature of the quaternary ammonium salt surfactant can interact with the negatively charged groups of the oil phase, effectively promoting the affinity between the aqueous and oil phases, further increasing the crosslinking density of the polymer, and enhancing the stability of the polysulfonate film composite membrane. In addition, quaternary ammonium salt surfactants can finely adjust the pore size and pore size distribution of polysulfonate film composite membranes by controlling their concentration and type, thereby optimizing the separation performance of polysulfonate film composite membranes and achieving good selectivity and flux.
[0042] In a further embodiment, the second surfactant comprises any one or a combination of two or more of the following: dioctadecyl dimethyl ammonium chloride, dioctadecyl dimethyl ammonium bromide, dihexadecyl dimethyl ammonium chloride, dihexadecyl dimethyl ammonium bromide, didodecyl dimethyl ammonium chloride, didodecyl dimethyl ammonium bromide, didecyl dimethyl ammonium chloride, didecyl dimethyl ammonium bromide, dioctadecyl dimethyl ammonium chloride, and dioctadecyl dimethyl ammonium bromide. In this embodiment, the second surfactant is a quaternary ammonium surfactant, which has strong interfacial activity and can effectively reduce interfacial tension and promote the stability of the oil-water interface. This allows the polyhydroxy monomers in the aqueous solution to react more uniformly with the polysulfonyl chloride monomers in the oil solution, thereby ensuring a more uniform formation of the polysulfonate separation layer and reducing surface defects in the polysulfonate film composite membrane.
[0043] In a further embodiment, the porous support membrane is a polyethersulfone ultrafiltration membrane. In this embodiment, using a polyethersulfone ultrafiltration membrane as the porous support membrane provides a stable support structure and resistance to erosion by various chemicals such as acids, alkalis, and oxidants. It also provides appropriate porosity while maintaining good fluid flux, ensuring the mechanical strength, structural stability, and fluid flux of the polysulfonate film composite membrane based on the porous support membrane. Here, the effective pore size of the porous support membrane is any value between 5nm and 100nm, that is, the effective pore size of the porous support membrane can be 5nm, 10nm, 50nm, 80nm, or 100nm, or any value between 5nm and 100nm. In other embodiments, the porous support membrane can also be any one or a combination of two or more of the following: polyvinylidene fluoride ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, polysulfone ultrafiltration membrane, and nanocomposite ultrafiltration membrane.
[0044] In a further embodiment, the thickness of the polysulfonate separation layer is any value between 10 nm and 300 nm. That is, the thickness of the polysulfonate separation layer in the polysulfonate film composite membrane can be 10 nm, 20 nm, 30 nm, 50 nm, 100 nm, 150 nm, 200 nm, or 300 nm, or any value between 10 nm and 300 nm. By setting the thickness of the polysulfonate separation layer within the above range, the polysulfonate film composite membrane can be guaranteed to have strong mechanical stability and impact resistance, while also ensuring the permeation flux of the polysulfonate film polymer membrane, thereby ensuring the selectivity and separation performance of the polysulfonate film composite membrane.
[0045] like Figure 1 As shown, the present invention also provides a method for preparing the polysulfonate film composite film according to any one of the above claims, characterized by comprising the following steps:
[0046] Step S100: Coat the surface of the porous support membrane with an aqueous solution containing polyhydroxy monomers and let it stand for a first preset time under a first preset temperature and preset relative humidity conditions.
[0047] Step S200: Coat the surface of the porous support membrane with an oil phase solution containing polysulfonyl chloride monomer and let it stand for a second preset time to prepare a composite membrane;
[0048] Step S300: After annealing the composite film, a polysulfonate film composite film is obtained, wherein the first preset temperature is any value between 15℃ and 40℃, the preset relative humidity is any value between 20% and 80%, the annealing temperature is any value between 30℃ and 90℃, and the annealing time is any value between 5min and 60min.
[0049] In this embodiment, an aqueous solution containing polyhydroxy monomers is first coated onto the surface of a porous support membrane, and then left to stand for a first preset time under a first preset temperature and a preset relative humidity. Next, an oil solution containing polysulfonyl chloride monomers is coated onto the surface of the porous support membrane that has been coated with the aqueous solution, and left to stand for a second preset time to prepare a composite membrane. After annealing the composite membrane, a polysulfonate film composite membrane is obtained. The molecular weight cutoff of the polysulfonate film composite membrane prepared in this embodiment can be adjusted to any value between 100 Da and 2000 Da to meet the separation requirements of ions or molecules of different molecular weights.
[0050] In this embodiment, after coating the porous support membrane surface with an aqueous solution containing polyhydroxy monomers, the membrane is left to stand for a first preset time under a first preset temperature and a preset relative humidity. This ensures that the polyhydroxy monomers in the aqueous solution are in full contact with the porous support membrane surface, allowing the polyhydroxy monomers to be uniformly adsorbed or wetted on the porous support membrane surface. The first preset temperature can be 15°C, 20°C, 25°C, 30°C, 35°C, or 40°C, or any value between 15°C and 40°C. The preset relative humidity is 20%, 40%, 60%, or 80%, or any value between 20% and 80%. This allows the polyhydroxy monomers to quickly and uniformly penetrate the porous support membrane surface, helping to maintain the uniformity and wettability of the porous support membrane surface and preventing uneven drying or defects on the porous support membrane surface caused by excessively rapid evaporation due to high temperature or low relative humidity. Here, the first preset time is any value between 10s and 300s. The first preset time can be 10s, 20s, 50s, 100s, 150s, 200s, 240s or 300s, or any value between 10s and 300s.
[0051] In this embodiment, the annealing temperature is any value between 30℃ and 90℃, and the annealing time is any value between 5min and 60min. That is, the annealing temperature can be 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, or 90℃, or any value between 30℃ and 90℃, and the annealing time can be 5min, 10min, 20min, 30min, 45min, or 60min, or any value between 5min and 60min. By setting the annealing temperature and time within the above ranges, the molecular chains of the polysulfonate film composite membrane will gradually expand, and the thermoplasticity of the membrane material will begin to appear. This helps to enhance the mechanical strength and structural density of the polysulfonate film composite membrane, and also helps to homogenize the surface morphology, pore distribution, and cross-linking effect of the polysulfonate film composite membrane surface, further enhancing the selectivity, separation performance, chemical resistance, and antifouling ability of the polysulfonate film composite membrane. Here, the organic solvent in the oil phase solution is n-hexane.
[0052] In this embodiment, the second preset time can be any value between 10s and 1800s. That is, the settling time after coating the oil phase solution containing polysulfonyl chloride monomers onto the surface of the porous support membrane can be 10s, 50s, 100s, 200s, 500s, 1000s, 1500s, or 1800s, or any value between 10s and 1800s. By setting the settling time within the above range after coating the oil phase solution containing polysulfonyl chloride monomers onto the surface of the porous support membrane, it is ensured that the polysulfonyl chloride monomers can be uniformly distributed on the surface of the porous support membrane, facilitating subsequent interfacial polymerization at the water / oil interface, thereby further improving the structural uniformity and density of the polysulfonate film composite membrane.
[0053] In a further embodiment, the concentration of the polyhydroxy monomer in the aqueous solution is any value between 0.5 g / L and 40 g / L. That is, the concentration of the polyhydroxy monomer in the aqueous solution can be 0.5 g / L, 1.0 g / L, 5.0 g / L, 10 g / L, 20 g / L, 30 g / L, or 40 g / L, or any value between 0.5 g / L and 40 g / L. In this embodiment, by setting the concentration of the polyhydroxy monomer in the aqueous solution within the above range, polysulfonate film composite membranes with different pore sizes can be prepared by controlling the concentration of the polyhydroxy monomer. This allows the prepared polysulfonate film composite membrane to be used for the selective separation of molecules or ions of different molecular weights, further improving the selectivity and separation performance of the polysulfonate film composite membrane.
[0054] In this embodiment, the concentration of the first surfactant is any value between 0.0001 g / L and 100 g / L. That is, when the first surfactant is selectively added to the aqueous solution, the concentration of the first surfactant in the aqueous solution can be 0.0001 g / L, 0.001 g / L, 0.01 g / L, 0.1 g / L, 1.0 g / L, 10 g / L, or 100 g / L, or any value between 0.0001 g / L and 100 g / L. By setting the concentration of the first surfactant in the aqueous solution within the above range, the interfacial stability, the reaction rate of the interfacial polymerization reaction, and the pore size of the polysulfonate film composite membrane can be controlled by changing the concentration of the first surfactant in the aqueous solution, so as to prepare a polysulfonate film composite membrane with strong mechanical strength, structural stability, and meeting the separation performance requirements.
[0055] In a further embodiment, the concentration of the polysulfonyl chloride monomer in the oil phase solution is any value from 0.5 g / L to 30 g / L. In this embodiment, the concentration of the polysulfonyl chloride monomer can be 0.5 g / L, 1.0 g / L, 5.0 g / L, 10 g / L, 20 g / L, 25 g / L, or 30 g / L, or any value from 0.5 g / L to 30 g / L. In this embodiment, by setting the polysulfonyl chloride monomer in the oil phase solution within the above range, the polysulfonyl chloride monomer in the oil phase solution can react completely with the polyhydroxy monomer in the aqueous phase solution at the water / oil interface, thereby preparing a polysulfonate film composite membrane with adjustable crosslinking density, dense membrane structure, and good separation performance, stability, and corrosion resistance.
[0056] In this embodiment, the concentration of the second surfactant is any value between 0.0001 g / L and 100 g / L. That is, when the second surfactant is selectively added to the oil phase solution, the concentration of the second surfactant in the oil phase solution can be 0.0001 g / L, 0.001 g / L, 0.01 g / L, 0.1 g / L, 1.0 g / L, 10 g / L, or 100 g / L, or any value between 0.0001 g / L and 100 g / L. By setting the concentration of the second surfactant in the oil phase solution within the above range, the pore size of the polysulfonate film composite membrane can be controlled by changing the concentration of the second surfactant in the oil phase solution, so as to prepare a polysulfonate film composite membrane with strong mechanical strength, structural stability, and meeting the separation performance requirements.
[0057] The present application will be further described in detail below with reference to specific embodiments.
[0058] In some embodiments, the porous support membrane in the polysulfonate film composite membrane is a polyethersulfone ultrafiltration membrane; the first surfactant in the aqueous solution is any one or a combination of two or more of tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, and octadecyltrimethylammonium chloride, and the concentration of the first surfactant is any value between 0.0001 g / L and 100 g / L; the polyhydroxy monomer in the aqueous solution can be any one or a combination of two of tannic acid or epigallocatechin gallate, and the concentration of the polyhydroxy monomer is any value between 0.5 g / L and 30 g / L. The polysulfonyl chloride monomer in the oil phase solution is any one of 1,3-benzenedisulfonyl chloride, 1,3,6-naphthalenetrisulfonyl chloride, and 1,3,6-naphthalenetrisulfonyl chloride, and the concentration of the polysulfonyl chloride monomer is any value between 0.5 g / L and 30 g / L. The second surfactant in the oil phase solution is any one or a combination of two or more of bis(octadecyl)dimethylammonium chloride, bis(hexadecyl)dimethylammonium chloride, and bis(tetradecyl)dimethylammonium chloride, and the concentration of the second surfactant is any value between 0.0001 g / L and 100 g / L, in order to prepare a polysulfonate film composite membrane with a molecular weight cutoff of any value between 100 Da and 2000 Da.
[0059] Example 1
[0060] A tannic acid solution with a concentration of 12 g / L was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 10 seconds at a preset temperature of 15°C and a preset relative humidity of 60% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution with a concentration of 2 g / L of 1,3-benzenedisulfonyl chloride. After standing for 180 seconds, the composite membrane was immersed in n-hexane to wash away excess 1,3-benzenedisulfonyl chloride. The membrane was then annealed and stored after being soaked in deionized water for 30 minutes at a temperature of 60°C.
[0061] The polysulfonate film composite membrane prepared in this embodiment was subjected to a retention rate test. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 1000ppm Na2SO4 aqueous solution. The test temperature was 25℃ and the operating pressure was 5 bar. The test results are shown in Table 1.
[0062] Example 2
[0063] An aqueous solution containing 12 g / L tannic acid and 0.38 g / L hexadecyltrimethylammonium chloride was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 120 seconds at a preset temperature of 25°C and a preset relative humidity of 60% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 2 g / L 1,3-benzenedisulfonyl chloride. After standing for 10 seconds, the composite membrane was immersed in n-hexane to wash away excess 1,3-benzenedisulfonyl chloride. The membrane was then annealed and stored after being soaked in deionized water for 30 minutes at a temperature of 90°C.
[0064] The polysulfonate film composite membrane prepared in this embodiment was subjected to a retention rate test. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 1000ppm Na2SO4 aqueous solution. The test temperature was 25℃ and the operating pressure was 5 bar. The test results are shown in Table 1.
[0065] Example 3
[0066] An aqueous solution containing 12 g / L tannic acid and 0.38 g / L hexadecyltrimethylammonium chloride was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 300 s at a preset temperature of 40°C and a preset relative humidity of 60% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 5 g / L 1,3-benzenedisulfonyl chloride and 0.1 g / L bis(octadecyldimethylammonium chloride). After standing for 120 s, the composite membrane was immersed in hexane to wash away excess 1,3-benzenedisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 30 min at a temperature of 60°C.
[0067] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15 bar. The above polysulfonate film composite membrane was then immersed in a 10% (w / v) sulfuric acid solution for 1 hour, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0068] Example 4
[0069] An aqueous solution containing 12 g / L tannic acid and 0.38 g / L hexadecyltrimethylammonium chloride was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 300 s at a preset temperature of 40°C and a preset relative humidity of 60% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 5 g / L 1,3-benzenedisulfonyl chloride and 0.1 g / L bis(octadecyldimethylammonium chloride). After standing for 120 s, the composite membrane was immersed in hexane to wash away excess 1,3-benzenedisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 30 min at a temperature of 60°C.
[0070] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15 bar. The above polysulfonate film composite membrane was then immersed in a 20% (w / v) sulfuric acid solution for 24 hours, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0071] Example 5
[0072] An aqueous solution containing 12 g / L tannic acid and 0.1 g / L hexadecyltrimethylammonium chloride was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 300 s at a preset temperature of 40°C and a preset relative humidity of 60% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil-phase solution containing 1 g / L 1,3-benzenedisulfonyl chloride and 0.05 g / L bis(octadecyldimethylammonium chloride). After standing for 120 s, the composite membrane was immersed in hexane to wash away excess 1,3-benzenedisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 10 min at a temperature of 60°C.
[0073] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15 bar. The above polysulfonate film composite membrane was then immersed in a 5% (w / v) sulfuric acid solution for 1 hour, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0074] Example 6
[0075] A tannic acid solution with a concentration of 15 g / L was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 300 seconds at a preset temperature of 40°C and a preset relative humidity of 60% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 5 g / L of 1,3-benzenedisulfonyl chloride and 0.05 g / L of bis(octadecyl)dimethylammonium chloride. After standing for 120 seconds, the composite membrane was immersed in hexane to wash away excess 1,3-benzenedisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 20 minutes at a temperature of 60°C.
[0076] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15 bar. The above polysulfonate film composite membrane was then immersed in a 10% (w / v) sulfuric acid solution for 24 hours, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0077] Example 7
[0078] An aqueous solution containing 8 g / L tannic acid and 0.38 g / L hexadecyltrimethylammonium chloride was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 60 seconds at a preset temperature of 30°C and a preset relative humidity of 50% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil-phase solution containing 5 g / L 1,3-benzenedisulfonyl chloride and 0.1 g / L bis(octadecyldimethylammonium chloride). After standing for 180 seconds, the composite membrane was immersed in hexane to wash away excess 1,3-benzenedisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 10 minutes at a temperature of 50°C.
[0079] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15 bar. The above polysulfonate film composite membrane was then immersed in a 10% (w / v) sulfuric acid solution for 2 hours, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0080] Example 8
[0081] A tannic acid solution with a concentration of 5 g / L was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 150 seconds at a preset temperature of 45°C and a preset relative humidity of 45% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 3 g / L of 1,3,5-benzenetrisulfonyl chloride and 0.1 g / L of bis(octadecyl)dimethylammonium chloride. After standing for 70 seconds, the composite membrane was immersed in hexane to wash away excess 1,3,5-benzenetrisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 15 minutes at a temperature of 50°C.
[0082] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 16 bar. The above polysulfonate film composite membrane was then immersed in a 10% (w / v) sulfuric acid solution for 2 hours, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0083] Example 9
[0084] A tannic acid solution with a concentration of 1 g / L was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 90 seconds at a preset temperature of 35°C and a preset relative humidity of 45% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 1 g / L of 1,3,6-naphthalenetrisulfonyl chloride and 0.02 g / L of dioctadecyldimethylammonium chloride. After standing for 70 seconds, the composite membrane was immersed in hexane to wash away excess 1,3,6-naphthalenetrisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 10 minutes at a temperature of 50°C.
[0085] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15.5 bar. The above polysulfonate film composite membrane was then immersed in a 10% (w / v) sulfuric acid solution for 10 hours, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0086] Example 10
[0087] A tannic acid solution with a concentration of 25 g / L was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 80 seconds at a preset temperature of 35°C and a preset relative humidity of 45% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 1 g / L of 1,3,6-naphthalenetrisulfonyl chloride and 0.02 g / L of dioctadecyldimethylammonium chloride. After standing for 90 seconds, the composite membrane was immersed in hexane to wash away excess 1,3,6-naphthalenetrisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 25 minutes at a temperature of 45°C.
[0088] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15.5 bar. The above polysulfonate film composite membrane was then immersed in a 10% (w / v) sulfuric acid solution for 8 hours, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0089] Example 11
[0090] An aqueous solution of epigallocatechin gallate with a concentration of 25 g / L was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 50 seconds at a preset temperature of 35°C and a preset relative humidity of 45% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 1 g / L of 1,3,5-benzenetrisulfonyl chloride and 0.06 g / L of dioctadecyl dimethyl ammonium chloride. After standing for 100 seconds, the composite membrane was immersed in hexane to wash away excess 1,3,5-benzenetrisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 8 minutes at a temperature of 70°C.
[0091] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 18 bar. The above polysulfonate film composite membrane was then immersed in a 10% (w / v) sulfuric acid solution for 8 hours, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0092] Example 12
[0093] An aqueous solution containing 10 g / L epigallocatechin gallate and 0.038 g / L hexadecyltrimethylammonium chloride was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 30 seconds at a preset temperature of 35°C and a preset relative humidity of 50% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 1 g / L 1,3,5-benzenetrisulfonyl chloride and 0.06 g / L bis(octadecyldimethylammonium chloride). After standing for 100 seconds, the composite membrane was immersed in hexane to wash away excess 1,3,5-benzenetrisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 8 minutes at a temperature of 70°C.
[0094] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 18 bar. The above polysulfonate film composite membrane was then immersed in a 15% (w / v) sulfuric acid solution for 15 hours, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0095] Example 13
[0096] An aqueous solution containing 5 g / L epigallocatechin gallate and 0.38 g / L tetradecyltrimethylammonium chloride was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 150 s at a preset temperature of 45°C and a preset relative humidity of 45% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 3 g / L 1,3,5-benzenetrisulfonyl chloride and 0.1 g / L bis(octadecyldimethylammonium chloride). After standing for 70 s, the composite membrane was immersed in hexane to wash away excess 1,3,5-benzenetrisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 15 min at a temperature of 50°C.
[0097] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 16 bar. The above polysulfonate film composite membrane was then immersed in a 10% (w / v) sulfuric acid solution for 2 hours, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0098] Example 14
[0099] An aqueous solution containing 6 g / L epigallocatechin gallate and 0.24 g / L octadecyltrimethylammonium chloride was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 100 seconds at a preset temperature of 50°C and a preset relative humidity of 50% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 3 g / L 1,3,6-naphthalenetrisulfonyl chloride and 0.2 g / L hexadecyldimethylammonium chloride. After standing for 100 seconds, the composite membrane was immersed in hexane to wash away excess 1,3,6-naphthalenetrisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 20 minutes at a temperature of 55°C.
[0100] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 16 bar. The above polysulfonate film composite membrane was then immersed in a 16% (w / v) sulfuric acid solution for 1 hour, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0101] Example 15
[0102] An aqueous solution of epigallocatechin gallate with a concentration of 25 g / L was applied to the surface of a polyethersulfone ultrafiltration membrane. The membrane was then allowed to stand for 450 s at a preset temperature of 35°C and a preset relative humidity of 45% to prepare a polyethersulfone ultrafiltration membrane coated with tannic acid. The surface of the polyethersulfone ultrafiltration membrane was then immersed in an oil phase solution containing 1 g / L of 1,3,5-benzenetrisulfonyl chloride and 0.06 g / L of bis(tetradecyl)dimethylammonium chloride. After standing for 230 s, the composite membrane was immersed in hexane to wash away excess 1,3,5-benzenetrisulfonyl chloride. It was then annealed and stored after soaking in deionized water for 30 min at a temperature of 70°C.
[0103] The polysulfonate film composite membrane prepared in this embodiment was subjected to retention rate and acid resistance tests. Specifically, the flux, retention rate, and effective molecular weight cutoff of the polysulfonate film composite membrane were tested using a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15 bar. The above polysulfonate film composite membrane was then immersed in a 10% (w / v) sulfuric acid solution for 12 hours, and its flux and retention rate were then tested. The test results are shown in Table 1.
[0104] Comparative Example 1
[0105] The only difference between Comparative Example 1 and Example 1 is the composition of the oil phase solution. Specifically, the oil phase solution in Comparative Example 1 is a polyacrylamide chloride monomer solution, and the polyacrylamide chloride monomer in the oil phase solution is pyromellitic trimethylolpropionate chloride.
[0106] Comparative Example 2
[0107] The only difference between Comparative Example 2 and Example 4 is the composition of the oil phase solution. In Comparative Example 1, the oil phase solution is a polyacrylamide chloride monomer solution, specifically, the polyacrylamide chloride monomer in the oil phase solution is trimesoyl pyromellitic chloride. The flux and rejection rate of the thin film composite membrane prepared in Comparative Example 2 were tested after being immersed in 20% (w / v) sulfuric acid solution for 12 hours.
[0108] Comparative Example 3
[0109] The only difference between Comparative Example 3 and Example 4 is the composition of the oil phase solution. Specifically, the oil phase solution in Comparative Example 1 is a polyacrylamide chloride monomer solution, and the polyacrylamide chloride monomer in the oil phase solution is isophthaloyl chloride. The flux and rejection rate of the thin film composite membrane prepared in Comparative Example 3 were tested after being immersed in 20% (w / v) sulfuric acid solution for 12 hours.
[0110] Table 1. Retention rate and acid resistance test results of the thin film composite membranes prepared in Examples 1-14 and Comparative Examples 1-3
[0111]
[0112]
[0113] Figure 2 These are TEM images of the polysulfonate film composite membranes prepared in Examples 3-5 of this invention. Figure 3 The data is based on the AFM images of the polysulfonate film composites prepared in Examples 3-5 of this invention. Figure 4 This is a test chart showing the acid resistance of the polysulfonate film composite film prepared according to Example 3 of the present invention. Figure 5 This is a test diagram of the acid resistance of the polysulfonate film composite film prepared in Example 4 of the present invention.
[0114] As shown in Table 1, Figure 4 and Figure 5As shown, the polysulfonate film composite membranes prepared in Examples 3-15 exhibit strong acid resistance. They maintain a high rejection rate even after immersion in different acidic conditions for varying times, indicating that the polysulfonate film composite membranes prepared in this invention possess strong acid resistance and structural stability, resisting corrosion from strong acid solutions, thereby improving the acid resistance and service life of the polysulfonate film composite membranes in this invention. In contrast, the film composite membranes prepared in Comparative Examples 1-3, after immersion in 20% (w / v) sulfuric acid solution for 12 hours, showed a significant decrease in flux and rejection rate, indicating that the film composite membranes prepared from acyl chloride monomers have extremely poor acid resistance and cannot achieve the desired molecule rejection under acidic conditions. In contrast, the polysulfonate film composite membranes prepared in Examples 1 and 3 maintained high flux and rejection rates even after immersion in 20% (w / v) sulfuric acid solution for 24 hours, demonstrating that the polysulfonate film composite membranes prepared based on polysulfonyl chloride monomers have extremely strong acid resistance.
[0115] As shown in Table 1, polysulfonate membrane nanofiltration membranes were prepared in Examples 1 and 2, with molecular weight cutoffs of 1624 Da and 1520 Da, respectively. Polysulfonate membrane reverse osmosis membranes were prepared in Examples 3-15, with molecular weight cutoffs of 100 Da-368 Da. That is, the polysulfonate membrane composite membranes prepared by the present invention can be either polysulfonate membrane nanofiltration membranes or polysulfonate membrane reverse osmosis membranes, and polysulfonate membrane composite membranes with corresponding pore sizes can be prepared according to the required molecular weight cutoff.
[0116] like Figure 2 and Figure 3 As shown in the AFM diagrams of the polysulfonate film composite membranes prepared in Examples 3-5, Rq is 2.64 nm and Ra is 2.06 nm. That is, the Rq value in the AFM diagram is approximately equal to the Ra value, indicating that the surface of the prepared polysulfonate film composite membrane is relatively smooth and its surface fluctuation is relatively uniform, thereby ensuring the durability and separation performance of the polysulfonate film composite membrane.
[0117] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0118] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A polysulfonate film composite film, characterized in that, It includes a porous support membrane and a polysulfonate separation layer, wherein the polysulfonate separation layer is prepared by interfacial polymerization of an aqueous solution and an oil solution; wherein, The aqueous phase solution comprises a polyhydroxy monomer and a selectively added first surfactant, and the oil phase solution comprises a polysulfonyl chloride monomer and a selectively added second surfactant.
2. The polysulfonate film composite film according to claim 1, characterized in that, The polyhydroxy monomers include any one or a combination of two or more of the following: tannic acid, protocatechuic acid, gallic acid, ellagic acid, anthocyanins, proanthocyanidins, bisphenol A, epigallocatechin gallate, epigallocatechin, gallocatechin, gallocatechin gallic acid, catechuic acid, epicatechin, epicatechin gallate, quercetin, curcumin, cyclodextrin, sodium alginate, and resveratrol.
3. The polysulfonate film composite film according to claim 2, characterized in that, The first surfactant is a water-soluble surfactant, which includes any one or a combination of two or more of quaternary ammonium salt surfactants and heterocyclic surfactants.
4. The polysulfonate film composite film according to claim 3, characterized in that, The quaternary ammonium salt type surfactant includes any one or a combination of two or more of the following: octaalkyltrimethylammonium chloride, octaalkyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, docosyltrimethylammonium chloride, and docosyltrimethylammonium bromide.
5. The polysulfonate film composite film according to claim 4, characterized in that, The second surfactant includes any one or a combination of two or more of the following: dioctadecyl dimethyl ammonium chloride, dioctadecyl dimethyl ammonium bromide, dihexadecyl dimethyl ammonium chloride, dihexadecyl dimethyl ammonium bromide, didodecyl dimethyl ammonium chloride, didodecyl dimethyl ammonium bromide, didecyl dimethyl ammonium chloride, didecyl dimethyl ammonium bromide, dioctadecyl dimethyl ammonium chloride, and dioctadecyl dimethyl ammonium bromide.
6. The polysulfonate film composite film according to claim 5, characterized in that, The porous support membrane is a polyethersulfone ultrafiltration membrane.
7. The polysulfonate film composite film according to any one of claims 1-6, The thickness of the polysulfonate separation layer is any value between 10 nm and 300 nm.
8. A method for preparing a polysulfonate film composite film according to any one of claims 1-7, characterized in that, Includes the following steps: An aqueous solution containing multiple hydroxyl monomers is coated onto the surface of a porous support membrane and left to stand for a first preset time under a first preset temperature and preset relative humidity conditions. An oil phase solution containing polysulfonyl chloride monomers is coated onto the surface of the porous support membrane and left to stand for a second preset time to prepare a composite membrane. The composite film is annealed to obtain a polysulfonate film composite film; wherein... The first preset temperature is any value between 15℃ and 40℃, the preset relative humidity is any value between 20% and 80%, the annealing temperature is any value between 30℃ and 90℃, and the annealing time is any value between 5min and 60min.
9. The polysulfonate film composite film according to claim 8, characterized in that, The concentration of the polyhydroxy monomer in the aqueous solution is any value between 0.5 g / L and 40 g / L.
10. The polysulfonate film composite film according to claim 9, characterized in that, The concentration of the polysulfonyl chloride monomer in the oil phase solution is any value between 0.5 g / L and 30 g / L.